Minority Education in Greece: Thrace Muslim Teachers’ Approaches and Views - Zachos, Dimitris T. (Preschool and Primary Education, 2020)
In this paper, our focus is on the education of children from the Muslim Minority in Western Thrace, an administrative region of Greece. Education in Thrace is a sensitive issue that affects and is influenced by the bilateral relations between Greece and Turkey. More specifically, our research aimed to explore teachers of Muslim origins’ approaches, views and beliefs regarding Muslim students’ schooling. To this end, our research explored these issues in a Case Study using semi-structured interviews of Muslim teachers in Thrace. Our findings show that the policy of positive discrimination that had been applied to members of the Muslim Minority of Western Thrace for more than twenty years, has had positive results, but has now reached its limits. We believe that the findings of our research can inform policy makers, colleges and schools of education, as well as teachers by providing a better understanding of Muslim teachers’ prospects and needs.